The three geologic regions of Puebla State, Mexico - Gilberto Silva-Romo; Claudia Cristina Mendoza-Rosales; Wendy Vanesa Morales Barrera; Yoalli Bianii Hernández-Marmolejo (Journal of Maps)
Puebla State, Mexico, stands out with its diverse geological features, ranging from Precambrian and Paleozoic crystalline basements to the Pliocene-Quaternary major volcanoes. It is divided into three distinct regions: the northern region with its predominantly marine successions, where outcrops a volcano-sedimentary marine succession aged between 171.3 ± 0.5 Ma and 168.6 ± 0.4 Ma; the central region, part of the Trans-Mexican Volcanic Belt; and the southern region, mainly characterized by a multitude of continental units on crystalline basements.BULLETS:Geological regionalization, geological provinces, genetic-chronostratigraphic units, key successions tableGeological records contrast between the northern and southern regionsFirst report of Middle Jurassic marine volcano-sedimentary succession in the Sierra Madre Oriental Range